Use of Granisetron for prevention of hypotension and bradycardia due to spinal anesthesia: A double blind randomised control trial - Shrestha, Battu Kumar; Acharya, Subhash Prasad; Marhatta, Moda Nath (Journal of Society of Anesthesiologists of Nepal, 2015)
Background: The common adverse effects of spinal anaesthesia include hypotension and bradycardia are due to sympathetic nerve blockade and activation of the Bezold-Jarisch reflex. The Bezold-Jarisch reflex in spinal anaesthesia may be mediated by peripheral 5-HT3 type serotonin receptors. We hypothesized that blockade of type 3 serotonin receptors by using intravenous Granisetron might reduce hypotension and bradycardia induced by spinal anaesthesia. Methodology: Sixty American Society of Anesthesiologists Physical Status I and II patients undergoing lower abdominal surgeries were randomized to receive either Normal Saline (control) or Granisetron 40 mcg/kg intravenously five minutes before subarachnoid block. Heart rates, systolic blood pressure, diastolic blood pressure, mean arterial pressure was recorded every two minutes for ten minutes and then every five minutes for another twenty minutes. Hemodynamic parameters were compared with baseline in each group. Results: There was decrease in all measured variables when compared with baseline values in both groups. There was less reduction in diastolic blood pressure in Granisetron group statistically significant at 10, 15, 20, 25 and 30 minutes. However, the less decrease in mean arterial pressure was statistically significant at 30 minutes only. There were no significant differences in systolic blood pressure and heart rate values between the groups. Conclusions: Granisetron given intravenously does not decrease the incidence of hypotension and bradycardia following subarachnoid block in patients undergoing lower abdominal surgery. However, it attenuates the fall of diastolic and mean arterial pressure spinal anaesthesia. Journal of Society of Anesthesiologists 2014 1(1): 36-39